Should known allergy status be included as a medication administration ‘right’? - Mortell, Manfred (MAG ONLINE LIBRARY (MA Healthcare Ltd,), 2019)
This article employs a paediatric case study, involving a 3-year-old child who had an anaphylactic reaction that occurred as a result of the multidisciplinary team’s failure to identify and acknowledge the patient’s documented ‘known allergy’ status. It examines and reconsiders the ongoing healthcare dilemma of medication errors and recommends that known allergy status should be considered the second medication administration ‘right’ before the prescribing, transcribing, dispensing and administration of any drug. Identifying and documenting drug allergy status is particularly important when caring for paediatric patients, because they cannot speak for themselves and must rely on their parents, guardians or health professionals as patient advocates. The literature states that medication errors can be prevented by employing a ‘rights of medication administration’ format, whether that be the familiar ‘5 rights’ or a more detailed list. However, none of these formats specify known allergy status as a distinct ‘right’. The medication safety literature is also found wanting in respect of the known allergy status of the patient. When health professionals employ a medication administration rights format prior to prescribing, transcribing, dispensing or administering a medication, the ‘known allergy status’ of the patient should be a transparent inclusion.